Wound patch for preventing skin scar formation and preparation method thereof
By using electrospinning process in the wound patch, combining silk fibroin and metal ions, the high breathability and biocompatibility of the wound patch are achieved, the drug release curve is extended, and the wound in the existing technology is solved The lack of air permeability, biocompatibility and cost can effectively prevent and inhibit scar formation.
Patent Information
- Application Number
- CN202411323979.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing wound patches have shortcomings in breathability, biocompatibility and cost, making it difficult to effectively prevent the formation of hyperplastic scars and affect the wound healing process.
A composite film containing an adhesive layer and a functional layer is adopted. The adhesive layer consists of a first silk fibroin and metal ions. The functional layer is a composite fiber with a core-shell structure. The core layer contains a second silk fibroin and angiogenesis inhibition. The shell contains the third silk fibroin, which is prepared by electrospinning process to achieve hysteresis release of biologically active ingredients to promote wound healing and inhibit scar formation.
It achieves high breathability, good biocompatibility and adhesion of wound patches, extends the drug release curve, promotes healing in the early stage and inhibits scar formation in the later stage, adapts to the entire wound healing cycle, and reduces patient discomfort.
Smart Images

Figure CN119258258A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biomedical materials, and in particular to a wound patch for preventing skin scar formation and a preparation method thereof. Background Art
[0002] Hypertrophic scar (HS) is a pathological scar that may appear during the healing process of wounds, which poses a major challenge to clinical treatment. This type of scar usually appears as hard, abnormally raised tissue, and compared with the surrounding normal skin, they have obvious changes in pigmentation and tissue elasticity. Hypertrophic scars not only affect the patient's appearance, but may also cause symptoms such as itching and chronic pain. In severe cases, they may even affect joint movement and limb function, bringing serious impacts to the patient's daily life and psychological state.
[0003] At present, the formation mechanism of hypertrophic scars is not fully understood. The formation of hypertrophic scars is related to multiple factors, including inflammatory response, the role of growth factors such as TGF-β1, changes in the extracellular matrix, and genetic factors. In addition, the trend of neovascularization and degeneration during wound healing also has a significant impact on wound healing degeneration. Segmented regulation of the wound healing process may help prevent scar formation.
[0004] Wound dressings that inhibit scar formation are special dressings that promote wound healing and reduce scar formation by providing a suitable healing environment. Wound dressings used clinically mainly include silicone wound dressings and hydrogel dressings. These two materials have a good fit on the wound, can help isolate external pollutants, and play a role in preventing infection. However, these dressings still need to be improved in terms of breathability, biocompatibility, and cost.
[0005] Based on this, it is necessary to develop a wound dressing that can prevent scar formation, has good biocompatibility and good breathability. Summary of the invention
[0006] Based on this, one or more embodiments of the present application provide a wound patch for preventing skin scar formation and a preparation method thereof. The wound patch can prevent skin scar formation and also has the function of promoting wound healing. At the same time, its material is biodegradable, biocompatible, breathable, and has good fit and adhesion to the wound, which can reduce the patient's discomfort.
[0007] The technical solution of this application includes the following contents:
[0008] An embodiment of the present application provides a wound patch for preventing skin scar formation, which includes a composite film including an adhesive layer and a functional layer;
[0009] The adhesion layer comprises a first silk protein and metal ions; the metal ions have at least one of antibacterial, anti-inflammatory and angiogenesis-promoting effects; the functional layer comprises a composite fiber with a core-shell structure;
[0010] The core of the composite fiber comprises a second silk fibroin and an angiogenesis inhibitor, and the shell comprises a third silk fibroin.
[0011] In one embodiment, the weight ratio of the first silk fibroin to the metal ion is (0.25-1.5):1.
[0012] In one embodiment, the weight ratio of the second silk fibroin to the angiogenesis inhibitor is (10-500):1; and / or
[0013] The weight ratio of the core to the shell of the composite fiber is 1:(2-20).
[0014] In one embodiment, the metal ions include Ca 2+ 、Zn 2+ , Cu 2+ 、Ag + Mg 2+ 、Eu 3+ , Fe 3+ and Mn 2+ One or more of; and / or
[0015] The angiogenesis inhibitor includes at least one of green tea polyphenols, quercetin, delphinidin, apigenin, luteolin, geraniol, calla glycoside, anthocyanidin, pelargonium glycoside, morning glory glycoside, peony glycoside, chlorogenic acid, p-coumaric acid, red raspberry, bevacizumab, ramucirumab, olatumumab, anlotinib and sorafenib.
[0016] In one embodiment, the shell further comprises plant polyphenols;
[0017] Optionally, the weight ratio of the third silk fibroin to the plant polyphenol is (10~1000):1.
[0018] Another embodiment of the present application provides a method for preparing the wound dressing as described above, comprising:
[0019] The first silk fibroin, metal salt and first solvent are mixed and subjected to a first film-forming treatment to obtain the adhesion layer;
[0020] mixing the second silk fibroin, the angiogenesis inhibitor and a second solvent to obtain a core layer spinning solution;
[0021] mixing the third silk fibroin and the third solvent to obtain a shell spinning solution;
[0022] The core layer spinning solution and the shell layer spinning solution are electrospun by coaxial electrospinning process to obtain the composite fiber, and the adhesion layer is used as a receiving plate to form a functional layer on the adhesion layer of the composite fiber to obtain the composite film.
[0023] In one embodiment, the weight ratio of the solutes in the core layer spinning solution and the shell layer spinning solution is 1:(2-20).
[0024] In one embodiment, after the third silk fibroin and the third solvent are mixed, plant polyphenols are added to the mixture to obtain the shell spinning solution;
[0025] Optionally, the weight ratio of the third silk fibroin to the plant polyphenol is (10~1000):1.
[0026] In one embodiment, the step of mixing the first fiber, the metal salt and the solvent and subjecting the mixture to a first film-forming treatment to prepare the adhesive layer comprises:
[0027] After mixing the first fiber, the metal salt and the solvent, a first solution is obtained;
[0028] The first solution is prepared into a thin film by a first electrostatic spinning method or a method of spreading and then evaporating to obtain the adhesion layer;
[0029] Optionally, the injection rate of the first solution is 0.05 mL / h~2 mL / h;
[0030] Optionally, the voltage of the first electrospinning is 10 kV to 25 kV, and the collection distance is 10 cm to 20 cm.
[0031] In one embodiment, the step of electrospinning the core layer spinning solution and the shell layer spinning solution to obtain the composite fiber by a coaxial electrospinning process comprises:
[0032] The core layer spinning solution and the shell layer spinning solution are subjected to a second electrospinning process by a coaxial electrospinning device, wherein the inner diameter of the outer needle of the nozzle of the coaxial electrospinning device is 0.86 mm to 1.4 mm, and the outer diameter of the inner needle is 0.31 mm to 0.6 mm;
[0033] Optionally, the injection speed of the core layer spinning solution is 0.05 mL / h~2 mL / h, and the injection speed of the shell layer spinning solution is 0.1 mL / h~5 mL / h;
[0034] Optionally, the voltage of the second electrospinning is 10 kV to 25 kV, and the collection distance is 10 cm to 20 cm.
[0035] The wound patch for preventing skin scar formation of the present application has at least the following beneficial effects:
[0036] (1) The wound dressing of the present application can be flexibly and conveniently adhered to the wound surface, does not require additional fixing devices, and has the advantages of being easy to use and having a variety of application scenarios.
[0037] (2) The adhesive layer and the functional layer of the wound dressing of the present application are formed in an integrated manner. Due to the shielding of the adhesive layer and the core-shell structure design of the functional layer, the angiogenesis-inhibiting active ingredients of the functional layer can achieve the function of delayed release, so that the sequential regulation and step-by-step regulation of the entire wound healing process can be achieved: in the early stage of wound healing, the metal ions in the adhesive layer are first released to play a biologically active function, play an antibacterial, anti-inflammatory and angiogenesis-promoting effect, and promote wound healing. In some embodiments, the active substances in the shell layer of the functional layer are also gradually released in this link, which together play a role in preventing infection and promoting wound healing; in the later stage of wound healing, the angiogenesis inhibitor in the core of the functional layer is released to inhibit angiogenesis and excessive collagen proliferation, thereby effectively inhibiting scar formation. In this way, it has the overall effect of promoting healing in the early stage, avoiding infection, and preventing scars in the later stage, so as to adapt to the entire sequential cycle of normal wound healing.
[0038] (3) The composite film formed by the integrated wound dressing of the present application has excellent adhesion properties and suitable mechanical properties, and has good adhesion to the wound. Moreover, the film is made of silk fibroin, a natural polymer fiber material, and has good air permeability and low rejection, which greatly alleviates the itching, tingling and other problems that may occur to patients during the wound healing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0040] Figure 1 This is a laser confocal scanning image of the wound dressing of Example 1 of the present application;
[0041] Figure 2 1 is a transmission electron microscope image of the wound dressing of Example 2 and Comparative Example 1 of the present application;
[0042] Figure 3 is a scanning electron microscope image of the wound dressing prepared in Example 1 of the present application;
[0043] Figure 4This is a release curve of the anti-angiogenic substance EGCG of the wound dressing prepared in Example 1 of the present application;
[0044] Figure 5 The rabbit ear scar model healing test results of the wound dressings prepared in Example 1 and Comparative Example 1 of the present application;
[0045] Figure 6 The wound patch obtained in Example 2 and Comparative Example 1 of the present application was used to heal the wound model on the back of the rat.
[0046] Figure 7 These are the healing test results of the rat back wound model of the wound dressings prepared in Example 3 and Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0047] The present application will be further described below in conjunction with the embodiments and examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. In addition, it should be understood that after reading the content taught in the present application, those skilled in the art may make various changes or modifications to the present application, and these equivalent forms also fall within the protection scope of the claims attached to the present application.
[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0049] the term
[0050] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0051] The term "and / or" used in this article includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the arbitrary and all combinations include any two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in this application, the technical solution undoubtedly includes technical solutions that are all connected by "logical and", and undoubtedly includes technical solutions that are all connected by "logical or". For example, "A and / or B" includes three parallel solutions of A, B and A+B. For example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution that is all connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four of A, B, C, and D (that is, the technical solution that is all connected by "logical AND").
[0052] Herein, "preferred", "preferable", "better", etc. are only used to describe implementation methods or examples with better effects. It should be understood that they do not constitute limitations on the scope of protection of this application.
[0053] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0054] In this application, the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0055] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0056] In this application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.
[0057] In the present application, weight may be μg, mg, g, kg or other mass units known in the chemical industry.
[0058] In the present application, unless otherwise specified, the size, particle size and diameter generally refer to the average value.
[0059] In the present application, unless otherwise specified, the molecular weight refers to the average molecular weight, and further, unless otherwise specified, refers to the number average molecular weight.
[0060] An embodiment of the present application provides a wound patch for preventing skin scar formation, which includes a composite film including an adhesive layer and a functional layer;
[0061] The composition of the adhesion layer includes first silk fibroin and metal ions with antibacterial and anti-inflammatory effects;
[0062] The composition of the functional layer includes composite fibers having a core-shell structure;
[0063] The core of the composite fiber comprises the second silk fibroin and the angiogenesis inhibitor, and the shell comprises the third silk fibroin.
[0064] In the technical solution of the embodiment of the present application, the composite film is based on silk fibroin, so that it can have flexibility, suitable mechanical properties and is conducive to the close fit of each layer to each other, and is integrally formed. At the same time, it also has good biocompatibility and high fit to the wound surface. When in use, the adhesive layer in the composite film is directly attached to the wound surface, has good adhesion, and the released metal ions can play anti-inflammatory, antibacterial and promote angiogenesis, thereby promoting wound healing. The functional layer arranged on the adhesive layer includes a composite fiber with a core-shell structure. After the wound heals for a period of time, the active ingredient angiogenesis inhibitor in the core is gradually released, thereby avoiding scar formation.
[0065] In the technical solution of the embodiment of the present application, the adhesion layer is a fiber layer based on silk fibroin, which contains a suitable amount of metal ions with antibacterial and anti-inflammatory effects. The metal ions with antibacterial and anti-inflammatory effects include Ca 2+ 、Zn2+ , Cu 2+ 、Ag + Mg 2+ 、Eu 3+ , Fe 3+ and Mn 2+ One or more of .
[0066] Optionally, the weight ratio of the first silk fibroin and the metal ions is (0.25-0.5):1, so that the metal ions and the silk fibroin base have more suitable electrostatic interaction and chelating binding force, and better antibacterial and anti-inflammatory effects can be achieved when used.
[0067] Optionally, the weight ratio of the first silk fibroin to the metal ion can be (0.25-1.5):1, for example 0.25:1, 0.5:1, 0.75:1, 1:1, 1.25:1, 1.5:1, etc.
[0068] Optionally, metal ions with antibacterial and anti-inflammatory effects include Ca 2+ and Zn 2+ and Mg 2+ At least one of 2+ The molar proportion of metal ions with antibacterial and anti-inflammatory effects is 10% to 20%, and can further be 10% to 15%. In this way, combined with the structural characteristics of the silk fibroin base of the adhesive layer, it has a better effect of preventing infection in the early stage of wound healing. At the same time, the metal ions can also improve the adhesion of the silk fibroin-based adhesion layer and improve the biocompatibility of silk fibroin.
[0069] In the technical solution of the embodiment of the present application, the functional layer includes a composite fiber with a core-shell structure, the core is composed of a second silk fibroin and an angiogenesis inhibitor, and the shell is composed of a third silk fibroin.
[0070] In one embodiment, the shell also includes plant polyphenols, which can work together with the metal ions with antibacterial and anti-inflammatory effects to prevent infection and promote wound healing.
[0071] Optionally, the plant polyphenol and the angiogenesis inhibitor are different ingredients.
[0072] Optionally, the weight ratio of the third silk fibroin to the plant polyphenol can be selected from (100-1000): 1, for example 10: 1, 20: 1, 50: 1, 100: 1, 200: 1, 500: 1, 1000: 1, etc.
[0073] In one embodiment, the core comprises a second silk fibroin and an angiogenesis inhibitor, and the weight ratio of the second silk fibroin to the angiogenesis inhibitor is (10-500):1.
[0074] Optionally, the weight ratio of the second silk protein to the angiogenesis inhibitor can be (10-500):1, for example, 10:1, 50:1, 100:1, 200:1, 300:1, 500:1, etc. In the technical solution of the embodiment of the present application, the weight ratio of the core and the shell of the composite fiber can be 1:(2-20), for example, 1:2, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20, etc. In this way, the angiogenesis-inhibiting active ingredient in the core can be delayed released, and the release amount will not be reduced due to the obstruction of the shell layer, affecting the effect of preventing scar formation.
[0075] The angiogenesis inhibitor includes at least one of green tea polyphenols, quercetin, delphinidin, apigenin, luteolin, geraniol, anthocyanin, pelargonium glycoside, petuniin, peony glycoside, chlorogenic acid, p-coumaric acid, red raspberry, bevacizumab, ramucirumab, olatumumab, anlotinib and sorafenib.
[0076] An embodiment of the present application provides a method for preparing the above wound dressing, comprising:
[0077] The first silk fibroin, the metal salt and the first solvent are mixed and subjected to a first film-forming treatment to obtain an adhesion layer;
[0078] mixing the second silk fibroin, the angiogenesis inhibitor and the second solvent to obtain a core layer spinning solution;
[0079] mixing the third silk fibroin and the third solvent to obtain a shell spinning solution;
[0080] The core layer spinning solution and the shell layer spinning solution are electrospun by coaxial electrospinning process to obtain composite fibers, and the adhesion layer is used as a receiving plate to form a functional layer on the adhesion layer.
[0081] It can be understood that the material of the core layer spinning solution forms the core of the composite fiber, and the material of the shell layer spinning solution forms the shell of the composite fiber. The core layer spinning solution and the shell layer spinning solution are produced from a suitable nozzle through a coaxial electrospinning process under appropriate electrospinning conditions to form a composite fiber with a corresponding core-shell structure.
[0082] In one embodiment, the weight ratio of the solutes in the core layer spinning solution and the shell layer spinning solution is 1:(2-20).
[0083] In one embodiment, after the third silk fibroin and the third solvent are mixed, plant polyphenols are added to the mixture to obtain a shell spinning solution;
[0084] Plant polyphenols and angiogenesis inhibitors have different compositions;
[0085] Optionally, the weight ratio of the third silk fibroin to the plant polyphenols is (20~1000):1.
[0086] In one embodiment, the steps of mixing the first fiber, the metal salt and the solvent and subjecting the mixture to a first film-forming treatment to obtain the first film include:
[0087] After mixing the first fiber, the metal salt and the solvent, a first solution is obtained;
[0088] The first solution is prepared into a film by electrostatic spinning or by spreading and then evaporating to obtain a first film.
[0089] In one embodiment, the step of electrospinning the core layer spinning solution and the shell layer spinning solution to obtain the composite fiber by using a coaxial electrospinning process includes:
[0090] The core layer spinning solution and the shell layer spinning solution are electrospun through a coaxial electrospinning device, wherein the inner diameter of the outer needle of the nozzle of the coaxial electrospinning device is 0.86 mm to 1.4 mm, and the outer diameter of the inner needle is 0.31 mm to 0.6 mm;
[0091] Set the injection rate of the core layer spinning solution to 0.05mL / h~2mL / h, and the injection rate of the shell layer spinning solution to 0.1mL / h~5mL / h;
[0092] Optionally, the voltage of electrospinning is 10 kV to 25 kV, and the collection distance is 10 cm to 20 cm.
[0093] Compared with the traditional multi-layer wound dressing, the wound dressing using the technical solution of the present application can delay the initial release of the angiogenesis inhibitor (EGCG). There is basically no release in 0-3 days, and the release is accelerated around 3-7 days and continues to be stably released until about 14 days. This is because in the initial stage, the adhesion layer (the layer in contact with the wound) hinders the penetration of water molecules, thereby delaying the release of EGCG. As the wound heals, the adhesion layer gradually dissolves, and a small amount of EGCG physically adsorbed or weakly bound to the core-shell structure double-layer membrane nanofibers is continuously released. After 3-7 days, the release rate of EGCG is accelerated, but due to the diffusion mechanism of silk fibroin nanofibers and their slow degradation rate, the release of EGCG in the double-layer core-core bandage can continue for nearly 14 days.
[0094] The band-aid of the technical solution of the present application reduces the initial burst release, prolongs the drug sustained-release curve, allows the release of EGCG to be controlled for more than 14 days, achieves initial slow release and on-demand release, and provides support for the early anti-inflammatory and antioxidant effects of a small amount of EGCG in wound healing and the later sustained release of EGCG to inhibit angiogenesis.
[0095] The following are some specific embodiments.
[0096] For experimental parameters not specified in the following specific embodiments, reference is made to the instructions given in the present application document, and reference may also be made to experimental manuals in the art or other experimental methods known in the art, or to experimental conditions recommended by manufacturers.
[0097] The raw materials and reagents involved in the following specific examples can be obtained from commercial sources, or can be prepared by those skilled in the art according to known methods.
[0098] Example 1
[0099] This embodiment provides a method for preparing a wound dressing of the present application and its application in wound healing, as follows:
[0100] 1.1 Preparation of wound dressing
[0101] (1) Take NaHCO 3 Dissolve in 2L distilled water and boil, add 10g chopped cocoons, boil for 30min, wash the silk 4-5 times with 2L distilled water (60-70℃), dry in an oven (40-60℃), immerse the degummed silk in 9.3mol / L lithium bromide solution, dissolve in a drying oven at 60℃ for 4 hours, dialyze in deionized water for three days using a 1.2KD dialysis bag, freeze-dry into white fibers, and prepare purified silk fibroin.
[0102] (2) 0.2 g of calcium chloride, 0.02 g of zinc chloride, and 0.8 g of silk fibroin were dissolved in 8 mL of formic acid and spun into a first film by a first electrospinning process; the conditions for the first electrospinning process included: an electrospinning machine power supply voltage of 20 kV, a solution injection speed of 0.5 mL / h, and a collection distance of 15 cm.
[0103] (3) 0.01 g of EGCG was added to 5 mL of 10% silk fibroin formic acid solution to prepare the core layer spinning solution; 10 mL of 10% silk fibroin was used as the shell layer spinning solution, and the composite fiber was prepared using the coaxial electrospinning process conditions of the electrospinning apparatus, with the first film as the receiving layer and the power supply voltage of 20 kV; the injection rate of the core layer spinning solution was 0.5 mL / h, and the injection rate of the shell layer spinning solution was 1.5 mL / h; the inner diameter of the outer spray needle was 1 mm, and the inner diameter of the inner spray needle was 0.4 mm; the collection distance was 15 cm; the electrospinning collection membrane was collected and the volatile solvent was fully dried to obtain the wound dressing S1.
[0104] Example 2
[0105] This embodiment provides a method for preparing a wound dressing of the present application and its application in wound healing, as follows:
[0106] 1.1 Preparation of wound dressing
[0107] (1) Take NaHCO 3 Dissolve in 2L distilled water and boil, add 10g chopped cocoons, boil for 30min, wash the silk 4-5 times with 2L distilled water (60-70℃), dry in an oven (40-60℃), immerse the degummed silk in 9.3mol / L lithium bromide solution, dissolve in a drying oven at 60℃ for 4 hours, dialyze in deionized water for three days using a 1.2KD dialysis bag, freeze-dry into white fibers, and prepare purified silk fibroin.
[0108] (2) 0.2 g of calcium chloride, 0.02 g of magnesium chloride, and 0.8 g of silk fibroin were dissolved in 8 mL of formic acid and spun into a first film by a first electrospinning process; the conditions for the first electrospinning process included: an electrospinning machine power supply voltage of 20 kV, a solution injection speed of 0.5 mL / h, and a collection distance of 15 cm.
[0109] (3) 0.05 g of quercetin was added to 5 mL of 10% formic acid solution of silk fibroin to prepare the core layer spinning solution; 0.05 g of tannic acid was dissolved in 10 mL of 10% silk fibroin as the shell layer spinning solution, and the composite fiber was prepared by coaxial electrospinning process conditions of an electrospinning apparatus, with the first film as the receiving layer and a power supply voltage of 20 kV; the injection rate of the core layer spinning solution was 0.5 mL / h, and the injection rate of the shell layer spinning solution was 2 mL / h; the inner diameter of the outer spray needle was 1 mm, and the inner diameter of the inner spray needle was 0.5 mm; the collection distance was 15 cm; the electrospinning collection membrane was collected and the volatile solvent was fully dried to obtain the wound dressing S2.
[0110] Example 3
[0111] This embodiment provides a method for preparing a wound dressing of the present application and its application in wound healing, as follows:
[0112] 1.1 Preparation of wound dressing
[0113] (1) Take NaHCO 3 Dissolve in 2L distilled water and boil, add 10g chopped cocoons, boil for 30min, wash the silk 4-5 times with 2L distilled water (60-70℃), dry in an oven (40-60℃), immerse the degummed silk in 9.3mol / L lithium bromide solution, dissolve in a drying oven at 60℃ for 4 hours, dialyze in deionized water for three days using a 1.2KD dialysis bag, freeze-dry into white fibers, and prepare purified silk fibroin.
[0114] (2) 0.2 g of calcium chloride, 0.02 g of zinc chloride, and 2 g of silk fibroin were dissolved in 20 mL of formic acid and spun into a first film by a first electrospinning process; the conditions for the first electrospinning process included: an electrospinning machine power supply voltage of 20 kV, a solution injection speed of 0.5 mL / h, and a collection distance of 15 cm.
[0115] (3) 0.02 g of EGCG was added to 5 mL of 10% silk fibroin formic acid solution to prepare the core layer spinning solution; 0.1 g of anthocyanin was dissolved in 10 mL of 10% silk fibroin as the shell layer spinning solution, and the composite fiber was prepared using the coaxial electrospinning process conditions of an electrospinning apparatus, with the first film as the receiving layer and a power supply voltage of 25 kV; the injection rate of the core layer spinning solution was 0.5 mL / h, and the injection rate of the shell layer spinning solution was 2 mL / h; the inner diameter of the outer spray needle was 1 mm, and the inner diameter of the inner spray needle was 0.4 mm; the collection distance was 15 cm; the electrospinning collection membrane was fully dried to obtain the wound dressing S3.
[0116] Comparative Example 1
[0117] This comparative example provides a preparation method of a wound dressing of the present application and its application in wound healing, as follows:
[0118] 1.1 Preparation of wound dressing
[0119] (1) Take NaHCO 3 Dissolve in 2L distilled water and boil, add 10g chopped cocoons, boil for 30min, wash the silk 4-5 times with 2L distilled water (60-70℃), dry in an oven (40-60℃), immerse the degummed silk in 9.3mol / L lithium bromide solution, dissolve in a drying oven at 60℃ for 4 hours, dialyze in deionized water for three days using a 1.2KD dialysis bag, freeze-dry into white fibers, and prepare purified silk fibroin.
[0120] (2) 0.8 g of silk fibroin was dissolved in 8 mL of formic acid and spun into a first film by a first electrospinning process; the conditions for the first electrospinning process included: an electrospinning machine power supply voltage of 20 kV, a solution injection speed of 0.5 mL / h, and a collection distance of 15 cm.
[0121] (3) 5 mL of 10% silk fibroin formic acid solution was prepared as the core layer spinning solution; 10 mL of 10% silk fibroin was used as the shell layer spinning solution, and the composite fiber was prepared by the coaxial electrospinning process conditions of the electrospinning apparatus, with the first film as the receiving layer and the power supply voltage of 20 kV; the injection rate of the core layer spinning solution was 0.5 mL / h, and the injection rate of the shell layer spinning solution was 2 mL / h; the inner diameter of the outer spray needle was 1 mm, and the inner diameter of the inner spray needle was 0.31 mm; the collection distance was 15 cm; the electrospinning collection membrane was used and the volatile solvent was fully dried to obtain the wound dressing S4.
[0122] Comparative Example 2
[0123] This comparative example provides a preparation method of a wound dressing of the present application and its application in wound healing, as follows:
[0124] 1.1 Preparation of wound dressing
[0125] (1) Take NaHCO 3 Dissolve in 2L distilled water and boil, add 10g chopped cocoons, boil for 30min, wash the silk 4-5 times with 2L distilled water (60-70℃), dry in an oven (40-60℃), immerse the degummed silk in 9.3mol / L lithium bromide solution, dissolve in a drying oven at 60℃ for 4 hours, dialyze in deionized water for three days using a 1.2KD dialysis bag, freeze-dry into white fibers, and prepare purified silk fibroin.
[0126] (2) 0.5 g of calcium chloride, 0.1 g of zinc chloride, and 0.8 g of silk fibroin were dissolved in 8 mL of formic acid and spun into a first film by a first electrospinning process; the conditions for the first electrospinning process included: an electrospinning machine power supply voltage of 20 kV, a solution injection speed of 0.5 mL / h, and a collection distance of 15 cm.
[0127] (3) 0.02 g of EGCG and 0.1 g of anthocyanin were added to 15 mL of 10% silk fibroin formic acid solution to prepare the spinning solution; the first film was used as the receiving layer, the power supply voltage was 20 kV; the spinning solution was injected at a speed of 0.5 mL / h, and the collection distance was 15 cm; the electrospinning collection membrane was collected and the volatile solvent was fully dried to obtain the wound dressing S5.
[0128] 2. Performance Characterization
[0129] (1) Characterization of the internal structure of the functional layer of the wound dressing
[0130] The composite fiber was prepared by referring to step (3) of Example 1, except that rhodamine B and calcein were used to replace the inner layer EGCG and silk fibroin, respectively, and the composite fiber D1 was prepared using the coaxial process conditions of the electrospinning apparatus. A portion of the fiber was placed on a glass slide and observed under a laser scanning confocal microscope. The structure was as follows: Figure 1 As shown. Figure 1 The core layer of the composite fiber emits red fluorescence under 540 nm excitation, and the shell layer emits green fluorescence under 495 nm excitation, which confirms the successful preparation of the core-shell structure by coaxial electrospinning. The core-shell structure formed by coaxial electrospinning allows the carried therapeutic drugs or substances to be slowly released to meet the drug concentration requirements during tissue wound repair.
[0131] The composite fibers of Example 2 and Comparative Example 1 were observed under a transmission electron microscope. The results are as follows: Figure 2 As shown. Figure 2 The core layer and the shell layer of the composite fiber prepared in Example 2 have different densities, resulting in different brightness under the transmission electron microscope, which confirms that the core-shell structure is successfully prepared by coaxial electrospinning. The core-shell structure formed by coaxial electrospinning allows the carried therapeutic drugs or substances to be slowly released to meet the drug concentration requirements in the process of tissue wound repair.
[0132] (2) Characterization of overall morphology of wound dressing
[0133] Take the wound dressing S1 of Example 1, and use liquid nitrogen to brittle fracture, adhere the front side of the cross section to the conductive adhesive, spray gold and place it on a scanning electron microscope for observation. The results are as follows: Figure 3 shown.
[0134] according to Figure 3 It can be found that the lower adhesive layer of the wound dressing S1 is a thin film formed by a large number of silk protein filaments, in which calcium and zinc ions are evenly distributed. The upper functional layer is composed of composite fibers with a core-shell structure. The average size of the composite fibers is about 900 nm, with uniform morphology and a smooth surface.
[0135] (3) Active substance release test
[0136] Take the wound dressing S1 of Example 1, cut it into a suitable size, and fit it into the transwell chamber. The transwell chamber is immersed in a PBS solution in a 24-well plate at 37°C. The EGCG release amount is measured at a predetermined time point using a Shimadzu UV-2600 ultraviolet-visible spectrophotometer. The results are as follows: Figure 4 shown.
[0137] according to Figure 4It can be found that when a single-layer non-core-core layer, a single-layer core-core layer, and a double-layer core-core band-aid of Example 1 are placed on the Transwell chamber filter membrane, the single-layer non-core-core layer fiber shows a typical one-step release, and a higher proportion of EGCG is completely released in a short time (12h). In contrast, the single-layer core-core layer fiber shows a two-stage release behavior, 58% of EGCG is released within the first day, followed by a continuous slow release, reaching a cumulative release rate of 100% on the 7th day. In the case of the double-layer band-aid of Example 1, the presence of the lower adhesive layer hinders the penetration of water molecules, thereby delaying the release of EGCG. During the dissolution of the lower layer, a small amount of EGCG physically adsorbed or weakly bound to the core-shell structure double-layer membrane nanofibers is continuously released. However, after 3-5 days, the release rate of EGCG is accelerated, but due to the diffusion mechanism of SF nanofibers and their slow degradation rate, the release of EGCG in the double-layer core-core band-aid lasts for nearly 14 days. These results indicate that by using a double-layer core band-aid fiber structure, the initial burst release is reduced, the drug sustained-release curve is prolonged, and the release of EGCG is controlled for more than 14 days. This allows for an initial slow release and on-demand release, which supports the anti-inflammatory and antioxidant effects of a small amount of EGCG in wound healing in the early stage and the sustained release of EGCG in the later stage to inhibit angiogenesis.
[0138] (4) Rabbit ear scar model healing test
[0139] New Zealand white rabbits (3-4 months old) were anesthetized by intravenous injection of sodium pentobarbital (30 mg / kg), and three wounds were received on each ear using an 8 mm biopsy punch, and the perichondrium was completely removed with a scalpel. Subsequently, they were randomly divided into 3 groups: (1) blank control group, (2) comparative example 1 group, and (3) example 1 group. The wounds of the New Zealand white rabbits in the blank control group were treated with phosphate buffer (10 μL), and the wounds of the New Zealand white rabbits in the comparative example 1 group and example 1 group were completely covered with the wound membrane of the comparative example 1 group and the wound membrane of example 1, respectively. The gross images of the wounds were recorded on days 0, 3, 7, 14, 21, and 28. The rabbit ear tissues were taken for histological analysis on days 14, 21, and 28. The results are shown in Figure 2. Figure 5 shown.
[0140] according to Figure 5 It can be found that within 1 week, the wounds of the comparative example 1 group and the example 1 group healed faster, the wound epidermis of the example 1 group healed almost completely, while the wounds of the control group healed poorly, accompanied by exudation and bacterial infection. By the 14th day, the control group was not completely healed, the wound surface was raised, and it was dark red, and no obvious raised area was seen in the example 1. On the 21st and 28th days, the control group had obvious scabs, and the comparative example 1 group had severe protrusions locally. In contrast, the example 1 group was often flat, with obvious hair growth on the surface.
[0141] (5) Rat back scar model healing test
[0142] A full-thickness wound model of SD rats was established, and the experimental animals were randomly divided into a blank group, a comparative example group 1, and an example group 2. All animals were anesthetized by intraperitoneal injection of chloral hydrate (0.3 mg / kg), and then shaved on the back with an electric animal shaver, and finally the surgical site was completely exposed with a depilatory cream. Subsequently, 6 full-thickness wounds (diameter ~15 mm) were inflicted on the back of each rat with surgical scissors. After removing the wound skin, the comparative example group 1 and the example group 2 were covered with the SF membrane prepared in comparative example 1 and the wound membrane prepared in example 2, respectively, and the wound in the blank group was treated with 50 μL of phosphate buffer at pH 7.4. Wound photos were taken on days 0, 7, 14, and 21 after surgery, and the wound healing process was recorded and analyzed using Image J. The results are shown in the figure. Figure 6 and Figure 7 shown.
[0143] according to Figure 6 , through the rat full-thickness skin defect repair experiment, it was confirmed that the adhesive dressing prepared in Example 2 has the effect of promoting wound healing and inhibiting scar formation. According to the image of the rat back wound and the quantitative analysis of the wound diameter by ImageJ, the wound healing trend was monitored on the 0th, 3rd, 7th, 14th and 21st days. In the overall trend, the wound contraction rate of the adhesive dressing group prepared in Example 2 was significantly faster than that of the control group and other groups. By the 7th day, the difference in healing rate between the adhesive dressing group prepared in Example 2 and other groups could be seen. By the 14th day, the wound of the adhesive dressing group prepared in Example 2 was basically healed, leaving only a small scar. In contrast, the wounds of the other two groups were of different sizes, and the unhealed wound area of the control group was the largest. By the 21st day, except for the control group, all other groups had completely healed. These results show that the application of integrated silk fibroin-based Janus double-layer core-shell sustained-release adhesive bandage can promote wound healing.
[0144] according to Figure 7, through the rat full-thickness skin defect repair experiment, it was confirmed that the dressing in Example 3 has the effect of promoting wound healing and inhibiting scar formation, and the dressing prepared in the comparative example has no obvious promoting effect on wound healing. The experimental groups are Example 3 dressing, Comparative Example 2 dressing and a completely untreated group (control group). According to the image of the rat back wound and the quantitative analysis of the wound diameter by ImageJ, the wound healing trend was monitored on the 0th day, the 7th day and the 14th day. In the overall trend, the wound contraction speed of the Example 3 dressing was significantly faster than that of the control group and the Comparative Example 2 group. By the 7th day, the difference in healing speed between the Example 3 dressing and the control group and the Comparative Example 1 group can be seen. By the 14th day, the wound of the Example 3 dressing group was basically healed, leaving only a small scar. In contrast, the Comparative Example 2 dressing group was not much different from the control group, and both left larger wounds. Comparative Example 2 does not have a core-shell structure to slowly release anti-angiogenic substances, thereby prematurely inhibiting the formation of blood vessels, resulting in delayed wound healing.
[0145] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.
[0146] The technical features of the above-mentioned implementation modes and examples can be combined in any appropriate manner. To make the description concise, not all possible combinations of the technical features in the above-mentioned implementation modes and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0147] The above-described embodiments only express several implementation methods of the present application, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for those of ordinary skill in the art, without departing from the concept of the present application, several variations and improvements can also be made, which all belong to the protection scope of the present application. In addition, it should be understood that after reading the above-mentioned teaching content of the present application, those skilled in the art can make various changes or modifications to the present application, and the equivalent forms obtained also fall within the protection scope of the present application. It should also be understood that the technical solutions obtained by those skilled in the art on the basis of the technical solutions provided in the present application through logical analysis, reasoning or limited experiments are all within the protection scope of the claims attached to the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A wound patch for preventing skin scarring, characterized in that: It includes a composite film including an adhesive layer and a functional layer; The adhesion layer comprises a first silk protein and metal ions; the metal ions have at least one of antibacterial, anti-inflammatory and angiogenesis-promoting effects; The composition of the functional layer includes composite fibers having a core-shell structure; The core of the composite fiber comprises a second silk fibroin and an angiogenesis inhibitor, and the shell comprises a third silk fibroin.
2. The wound dressing according to claim 1, characterized in that: The weight ratio of the first silk fibroin to the metal ion is (0.25-1.5):
1.
3. The wound dressing according to claim 1, characterized in that: The weight ratio of the second silk fibroin to the angiogenesis inhibitor is (10-500):1; and / or The weight ratio of the core to the shell of the composite fiber is 1:(2-20).
4. The wound dressing according to any one of claims 1 to 3, characterized in that: The metal ions include Ca 2+ 、Zn 2+ , Cu 2+ 、Ag + Mg 2+ 、Eu 3+ , Fe 3+ and Mn 2+ One or more of; and / or The angiogenesis inhibitor includes at least one of green tea polyphenols, quercetin, delphinidin, apigenin, luteolin, geraniol, calla glycoside, anthocyanidin, pelargonium glycoside, morning glory glycoside, peony glycoside, chlorogenic acid, p-coumaric acid, red raspberry, bevacizumab, ramucirumab, olatumumab, anlotinib and sorafenib.
5. The wound dressing according to any one of claims 1 to 3, characterized in that: The shell also includes plant polyphenols; Optionally, the weight ratio of the third silk fibroin to the plant polyphenol is (10~1000):
1.
6. A method for preparing a wound dressing according to any one of claims 1 to 5, characterized in that: include: The first silk fibroin, metal salt and first solvent are mixed and subjected to a first film-forming treatment to obtain the adhesion layer; mixing the second silk fibroin, the angiogenesis inhibitor and a second solvent to obtain a core layer spinning solution; mixing the third silk fibroin and the third solvent to obtain a shell spinning solution; The core layer spinning solution and the shell layer spinning solution are electrospun by coaxial electrospinning process to obtain the composite fiber, and the adhesion layer is used as a receiving plate to form a functional layer on the adhesion layer of the composite fiber to obtain the composite film.
7. The preparation method according to claim 6, characterized in that: The weight ratio of the solutes in the core layer spinning solution and the shell layer spinning solution is 1:(2-20).
8. The preparation method according to claim 6 or 7, characterized in that: After mixing the third silk fibroin and the third solvent, plant polyphenols are added and mixed to obtain the shell spinning solution; Optionally, the weight ratio of the third silk fibroin to the plant polyphenol is (10~1000):
1.
9. The preparation method according to claim 6 or 7, characterized in that: The step of mixing the first fiber, the metal salt and the solvent and subjecting the mixture to a first film-forming treatment to prepare the adhesive layer comprises: After mixing the first fiber, the metal salt and the solvent, a first solution is obtained; The first solution is prepared into a thin film by a first electrostatic spinning method or a method of spreading and then evaporating to obtain the adhesion layer; Optionally, the injection rate of the first solution is 0.05 mL / h~2 mL / h; Optionally, the voltage of the first electrospinning is 10 kV to 25 kV, and the collection distance is 10 cm to 20 cm.
10. The preparation method according to claim 6 or 7, characterized in that: The step of electrospinning the core layer spinning solution and the shell layer spinning solution to obtain the composite fiber by using a coaxial electrospinning process comprises: The core layer spinning solution and the shell layer spinning solution are subjected to a second electrospinning process by a coaxial electrospinning device, wherein the inner diameter of the outer needle of the nozzle of the coaxial electrospinning device is 0.86 mm to 1.4 mm, and the outer diameter of the inner needle is 0.31 mm to 0.6 mm; Optionally, the injection speed of the core layer spinning solution is 0.05 mL / h~2 mL / h, and the injection speed of the shell layer spinning solution is 0.1 mL / h~5 mL / h; Optionally, the voltage of the second electrospinning is 10 kV to 25 kV, and the collection distance is 10 cm to 20 cm.
Citation Information
Patent Citations
Composite biological material patch and preparation method thereof
CN103908692A
Active silk fibroin porous material or active silk fibroin film, and preparation method thereof
CN110003518A
Silk fibroin membrane with function of regulating growth of vascular cells and preparation method thereof
CN110075309A
Silk fibroin microneedle patch for improving hypertrophic scars and preparation method of silk fibroin microneedle patch
CN114129505A
Preparation method of skin repair fiber membrane
CN115382001A
Cited By
Antioxidant, antibacterial and moisturizing patterned treatment skin dressing and preparation method thereof
CN119656362A